Seleção de suportes e protocolos de imobilização de lipases para a síntese enzimática de biodiesel - Mendes, Adriano Aguiar (Universidade Federal de São Carlos, 2009)
The objective of this thesis was to prepare and select immobilized lipase derivatives with high catalytic activity and thermal stability to mediate the biodiesel synthesis from palm and babassu oils by ethanolic route. The experimental work was carried out in two steps. In the first, different lipases sources, including lipases from Thermomyces lanuginosus (TLL), Candida antarctica type B (CALB), porcine pancreas (PPL), Bacillus thermocatenulatus (BTL2), Pseudomonas fluorescens (LPF) and Lipex® 100L were immobilized on different supports activated by several protocols using two immobilization methods, such as physical adsorption and multipoint covalent attachment. The following matrixes were used: agarose, Toyopearl, chitosan, alginate-chitosan, octyl-agarose, hexyltoyopearl and PHB and activating agents were: glutaraldehyde, epichlorohydrin and glycidol. As expected the immobilization procedure, support and lipase source affected the catalytic properties of the immobilized derivatives and their suitability for the proposed reaction. With an exception of PPL, all lipase preparations (TLL, PFL, Lipex® 100L and CALB) showed high alkaline stability under the immobilization conditions (72 h at pH 10.05) resulting in immobilized derivatives having high hydrolytic activities. The highest hydrolytic activities were obtained by TLL immobilized on glyoxyl-agarose, glyoxyl-chitosan-alginate-TNBS, epoxy-chitosan-alginate and Lipex® 100L immobilized on epoxy-chitosan-alginate and glyoxyl-agarose. Under non-aqueous media using butyl butyrate synthesis as a model system, TLL and PFL immobilized on glyoxyl-agarose and glyoxyl-amine-toyopearl showed similar conversions. The highest thermal stability were obtained for non-aminated BTL2 immobilized on glyoxyl-agarose 10BCL (Stability Factor- SF =2648) and chemically aminated (SF=4360), followed by aminated CALB immobilized on glyoxyl-agarose BCL (SF=290) and TLL immobilized on glyoxyl-agarose BCL (SF~300). Using chitosan-alginate, the highest thermal stability was obtained for TLL immobilized on chitosan-alginate-TNBS activated with glyoxyl groups and glutaraldehyde (SF=45). The immobilization of lipases BTL2, CALB and TLL on hydrophobic supports such as octyl-agarose and hexyl-toyopearl by physical adsorption allowed obtaining thermal stable derivatives. In addition, immobilized derivatives on poly-(hydroxybutyrate) (PHB) showed high catalytic activity in both hydrolysis and esterification reactions. In the second step and based on their catalytic properties under both aqueous and non-aqueous media as well as thermal stabilities the following immobilized derivatives: TLL and PFL immobilized on glyoxyl-agarose and glyoxyl-amine-Toyopearl, TLL immobilized on chitosan-alginate-TNBS activated with glyoxyl and glutaraldehyde; TLL, PFL, Lipex® 100L and CALB immobilized by physical adsorption on PHB were selected to mediate the synthesis of biodiesel from palm and babassu oils. For derivatives prepared by multipoint covalent attachment and under the conditions used, total conversion in ethyl esters was achieved within 24 to 48 h, depending on the vegetable oil. For immobilized derivatives prepared by physical adsorption on PHB, a slight higher reaction time (72 h) was needed to attain total conversion in ethyl esters. Despite its high esterification activity, BTL2 immobilized on PHB failed to mediate the ethanolysis of both vegetable oils. The viscosity values for the biodiesel samples (3.4-4.5 cSt) are in accordance with specifications recommended by the Brazilian Petroleum Agency (ANP) to be used as biofue.
Keywords: Tecnologia de enzimas; Imobilização; Lipase; Transesterificação; Biodiesel; Suportes; Supports; Lipases immobilization; Thermal stablization; Transesterification; Biodiesel; ENGENHARIAS::ENGENHARIA QUIMICA